Comparison between Lactobacillus Reuteri Probiotic in Addition to Standard Care versus Standard Care Alone in the Treatment of Infantile Colic: Lactobacillus Reuteri Probiotic in Addition to Standard Care in the Treatment of Infantile Colic - Maqsood, Shamaila; Naveed, Hina; Kafait, Yusra; Hafeez, Samia; Noor, Sidra; Waris, Rehmana; Ahsan, Muhammad (Pakistan Journal of Health Sciences, 2026)
Excessive crying is one of the most common problems in the first three months of life, accounting for nearly 20% of pediatric consultations. Objectives: To evaluate the effectiveness of Lactobacillus reuteri in infants with infantile colic compared with standard care alone. Methods: A prospective quasi-experimental study was used to enroll 172 infants (<13 weeks of age) with clinically diagnosed infantile colic who were enrolled. Group A received probiotic L. reuteri in addition to standard care, while Group B received standard care alone. Outcomes included mean daily crying time, crying episodes/week, and daily sleep duration, measured at baseline, days 7, 14, 21, and 28. Between-group comparisons were performed using the Mann–Whitney U test, and within-group changes were analyzed using the Friedman test. Results: Over 28 days, Group A showed greater improvement than Group B in reducing crying and increasing sleep. Daily crying decreased by −3.53 ± 1.05 hours in Group A vs. −1.79 ± 1.19 hours in Group B (p<0.001), weekly crying episodes by −3.60 ± 0.69 vs. −3.36 ± 0.97 (p=0.041), and daily sleep increased by 5.38 ± 2.08 hours vs. 2.80 ± 3.52 hours (p<0.001). Conclusions: L. reuteri supplementation in addition to standard care significantly reduced crying time and episodes, and improved sleep-in infants with colic compared to standard care alone.